2022
DOI: 10.1002/eom2.12269
|View full text |Cite
|
Sign up to set email alerts
|

Engineering current collectors for advanced alkali metal anodes: A review and perspective

Abstract: Alkali metal batteries (AMBs) are promising next-generation high-density electrochemical energy storage systems. In addition, current collectors play important roles in enhancing their electrochemical performances. Thus, it is essential to have a critical review of the most recent advances in engineering the current collectors for high-performance AMBs. In this review paper, the fundamentals of alkali metal deposition on current collectors will be introduced first. Then recent advances in the development of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 184 publications
0
18
0
Order By: Relevance
“…In addition, the F and LiF distributions of the artificially modified Li 3 BO 3 film are less than those of the original SEI film of the bare Li anode. The composition and content of the SEI film on the surface of the Li anode changed under the protection of the artificial Li 3 BO 3 film, which indicated that it reduced the side reactions between the metal Li anode and the liquid electrolytes. , Consequently, the artificial Li 3 BO 3 film can effectively alleviate the volume change of Li anodes, inhibit the growth of Li dendrites, and increase the cycling stability of the Li metal anode and the battery life.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the F and LiF distributions of the artificially modified Li 3 BO 3 film are less than those of the original SEI film of the bare Li anode. The composition and content of the SEI film on the surface of the Li anode changed under the protection of the artificial Li 3 BO 3 film, which indicated that it reduced the side reactions between the metal Li anode and the liquid electrolytes. , Consequently, the artificial Li 3 BO 3 film can effectively alleviate the volume change of Li anodes, inhibit the growth of Li dendrites, and increase the cycling stability of the Li metal anode and the battery life.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, measurable progress has been achieved in exploiting non-metal-based CCs. [76][77][78] Graphitic carbon-based CCs are the most representative non-metal collectors owing to their high conductivity and flexibility. 78 Graphite materials are primarily used as nucleation sites or protection layers to modify metallic CCs, such as vertically aligned graphene pillars on Cu foil, 79 porous carbon nanotube (CNT) sponge on Cu foil, 43 fluorinated electrochemically exfoliated graphene coated on Cu foil, 80 and graphene anchored on Cu foam.…”
Section: Beyond Cu Foilmentioning
confidence: 99%
“…Simultaneously, measurable progress has been achieved in exploiting non-metal-based CCs. 76–78 Graphitic carbon-based CCs are the most representative non-metal collectors owing to their high conductivity and flexibility. 78…”
Section: Beyond Cu Foilmentioning
confidence: 99%
“…14 In addition, there are many reports concerning the modification of the 3D skeleton to increase its lithiophilicity, for example, Co 3 O 4 nanoflower modified Ni foam, 15 3D graphene complexed with Ni foam, 16 3D hierarchical porous metal collectors, 17 MXene modified Cu foam, 18 ZnF 2 coated 3D Li-Ni composite anodes, 19 partly lithiated graphitic carbon foam, 20 metal-organic framework (MOF)-coated CNT, 21 coralloid carbon fiber-based Ag-Li composites, 22 ZnO quantum dot decorated porous carbon scaffolds, 23 Li-wicking host (denoted as GCF/Cu/Li), 24 Li deposited on Cu-coated CF (Li/CuCF), 25 Li-metal composite yarn (LMCY), 26 etc. [27][28][29] Apparently, multiple steps are involved in the preparation of a 3D skeleton or compositing with Li. Therefore, simplifying the fabrication process of the lithiophilic skeleton and increasing its Li affinity are the main research directions of the 3D conductive skeleton.…”
Section: Introductionmentioning
confidence: 99%